Two strategically placed base pairs in helix 8 of mammalian signal recognition particle RNA are crucial for the SPR19-dependent binding of protein SRP54 - YIN, JIAMING (Copyright 2004 by RNA Society, 2004)
Signal recognition particle (SRP) guides secretory proteins to biological membranes in all organisms. Assembly of the large domain of mammalian SRP requires binding of SRP19 prior to the binding of protein SRP54 to SRP RNA. The crystal structure of the ternary complex reveals the parallel arrangement of RNA helices 6 and 8, a bridging of the helices via a hydrogen bonded A149–A201 pair and protein SRP19, and two A minor motifs between the asymmetric loop of helix 8 (A213 and A214) and helix 6. We investigated which residues in helix 8 are responsible for the SRP19-dependent binding of SRP54 by taking advantage of the finding that binding of human SRP54 to Methanococcus jannaschii SRP RNA is independent of SRP19. Chimeric human/M. jannaschii SRP RNA molecules were synthesized containing predominantly human SRP RNA but possessing M. jannaschii SRP RNA-derived substitutions. Activities of the chimeric RNAs were measured with respect to protein SRP19 and the methionine-rich RNA-binding domain of protein SRP54 (SRP54M). Changing A213 and A214 to a uridine has no effect on the SRP19-dependent binding of SRP54M. Instead, the two base pairs C189–G210 and C190–G209, positioned between the conserved binding site of SRP54 and the asymmetric loop, are critical for conveying SRP19 dependency. Furthermore, the nucleotide composition of five base pairs surrounding the asymmetric loop affects binding of SRP54M significantly. These results demonstrate that subtle, and not easily perceived, structural differences are of crucial importance in the assembly of mammalian SRP.